Hubungan Karakteristik dalam Keluarga dengan Pengetahuan dan Sikap Siswi SMA Uswatun Hasanah Tentang Infeksi Menular Seksual (IMS) di Jakarta Timur - Alib Birwin (Jurnal Kesehatan Komunitas, 2014)
It is assumed that many young girls have risky sexual behavior because they have a lack of knowledge and negative attitude on sexual education; it means that the young girls have a lack of knowledge and negative attitude concerning sexual transmitted infection. The objective of this study is to examine several factors associated with knowledge and attitude of pupils of Uswatun Hasanah High School concerning sexual transmitted infection (STI). The method of study uses descriptive cross sectional study, the population and sample of this study is 60 pupils of Uswathun Hasanah High School in 2011. The dependent variables are knowledge and attitude about STI; each of them is associated with 8 independent variables. Collection of primary data was conducted through structural interview by using close ended question. Analysis of data is conducted for one variable and two variables by using x square test. The results of study shows that 1) The pupils of Uswatun Hasanah High School having low knowledge and negative attitude on STI was 41.7% and 36.7%; 2) Age of 15-16 years old, mother without occupation, family income < Rp. 1,300,000, and the number of family members > 3 persons were higher risk to have low knowledge on STI; 3) Father’s education of elementary school, family income < 1,300,000 and family member > 3 persons were higher risk to have negative attitude on STI; and 4) Low knowledge on STI is higher risk to have negative attitude on STI. Recommendation are to conduct further study using representative sample, to calculate sample size for analytic cross sectional study design, to conduct analysis of multi variables, and to detect the effectiveness of sexual education on the risk of sexual behavior. Suggestions are to conduct sexual education to the pupils of, and to conduct communication, information and education to the parents of Uswatun Hasanah High School in East Jakarta